Field CO2 enrichment by submarine vents unravels Zostera noltii response to ocean acidification - Arianna Pansini; Carmen Arena; Roberto Cabizza; Alessia Crobu; Ermenegilda Vitale; Giulia Ceccherelli (Marine Pollution Bulletin, 2026)

Effects of a simulated thermocline deepening on the biochemical composition of a Mediterranean seagrass - Patrizia Stipcich; Santina Soru; Giulia Ceccherelli; Francesco Palmas; Antonio Pusceddu (Marine Pollution Bulletin, 2026)

Erratum to “Short-term and long-term ocean acidification effects on seagrass performance: evidence from shallow CO2 vents” [Environ. Res. 285 (2025) 122485] - Arianna Pansini; Carmen Arena; Alessia Crobu; Ermenegilda Vitale; Giulia Ceccherelli (Environmental Research, 2026)

Holistic approach to restore marine ecosystems: RENOVATE project - Marco Marcelli; Sergio Scanu; Daniele Piazzolla; Simone Bonamano; Alice Madonia; Giorgio Fersini; Viviana Piermattei; Mar Bosch-Belmar; Francesco Paolo Mancuso; Giulia Ceccherelli; Annalisa Falace; Paola Del Negro; et al. (Frontiers in Marine Science, 2026)
Mediterranean coastal ecosystems are increasingly threatened by multiple anthropogenic pressures and climate change. As a result, these impacts have caused the decline of key endemic habitats such as Posidonia oceanica meadows and coralligenous reefs. Due to the slow natural recovery of these habitats after degradation, restoration actions play a key role in accelerating ecosystem recovery, reestablishing ecological structure and functional processes, and preventing further biodiversity and ecosystem service loss. Given the frequent habitat fragmentation and high levels of endemism, effective restoration efforts require a multidisciplinary, ecosystem-based approach that integrates marine science, engineering, socioeconomics, and policy. This study describes the holistic approach adopted in the RENOVATE project, which established an integrated framework to address the combined impacts of climate change and human pressures on vulnerable ecosystems. The framework employs advanced observational technologies, field data, and numerical modeling within an adaptive management loop, enabling site-specific, evidence-based restoration planning and assessment of ecosystem services recovery. Additionally, the study reports results from the northern Tyrrhenian coast (Latium, Italy), where RENOVATE aims to protect EU priority habitats and species from human pressures and climate-related threats. Although project activities are still in early stages, results from active restoration in the northern Latium coast show initial establishment and survival at pilot sites, highlighting the framework’s potential to guide effective, replicable interventions in coastal ecosystems. Beyond the regional case study, the proposed framework contributes to global marine restoration efforts by providing a transferable methodology for the management of coastal ecosystems.

Influence of red gorgonian (Paramuricea clavata) forests on coralligenous community structure across different regions, seasons, thermal environment, and water trophic state - La Manna Gabriella; Bolinesi Francesco; Bosch-Belmar Maria del Mar; Colletti Alberto; Di Marino Claudio; Fabietti Ylenia; Fraschetti Simonetta; Licciardi Luca; Mancuso Francesco Paolo; Mangoni Olga; Morello Giuseppe; Musumeci Simone Maria Santo; et al. (Coral Reefs, 2026)

Variation in Environmental Conditions and Biodiversity Between Contrasting Intertidal Habitats Across Multiple Spatial Scales on European Rocky Shores - Luca Rindi; Ludovica Pedicini; Iacopo Bertocci; Lisandro Benedetti‐Cecchi; Dan Smale; Fernando Tuya; Adriana Rodriguez; Mariachiara Chiantore; Valentina Asnaghi; Paolo Albicini; Rolf Karez; Dominique Davoult; et al. (Global Ecology and Biogeography, 2026)
Aim Foundation species sustain biodiversity by providing habitat, resources, and protection from environmental stress. However, their influence on environmental severity and variability and their role in shaping diversity across spatial scales remain poorly understood. We conducted a large‐scale study to assess how environmental conditions and community diversity vary between areas with and without canopy‐forming macroalgae across local to regional spatial scales. Location Latitudinal range from 28°34′N to 54°11′N, encompassing both the Northeast Atlantic and Western Mediterranean regions. Time Period 2019–2020. Major Taxa Studied Marine macroalgae and benthic invertebrates. Methods Using a standardised nested sampling design across 13 sites in two marine regions (the Northeast Atlantic and Western Mediterranean) we compared the intensity and variability of temperature and light intensity, as well as community α‐ and β‐diversity, between intertidal rocky areas with and without canopy‐forming macroalgae. Data were analysed by means of linear mixed‐effects models. Results There were regional differences in variations of environmental conditions between habitats: NE Atlantic macroalgal canopies were characterised by lower environmental extremes and variability—especially in summer—than open rock areas, whereas differences between habitats were small in the W Mediterranean. Likewise, differences in α‐ and β‐diversity between habitats were region‐specific and scale‐dependent: in the NE Atlantic, α‐diversity was higher in the presence of canopies than in open rock areas from local to regional scales, while β‐diversity decreased in canopy stands with increasing spatial scale. In the W Mediterranean, α‐diversity was higher under canopies than on open rock at the regional scale, whereas β‐diversity was higher under canopies at small to intermediate scales. Main Conclusions Our results support the view that key environmental conditions and biodiversity on intertidal rocky shores differ between areas characterised by the presence or absence of canopy‐forming macroalgae acting as foundation species, across a hierarchy of spatial scales.

Investigating drivers of Mediterranean coralligenous fish communities using passive acoustic monitoring: the role of thermal environment, day length and moon phases - Gabriella La Manna; Mariangela Moro Merella; Riccardo Vargiu; Giuseppe Morello; Gianluca Sarà; Giulia Ceccherelli (Marine Environmental Research, 2026)

Exploring the anatomical and metabolomic variabilities in the seagrass Posidonia oceanica (L.) Delile fruits - Federico Pinna; Mauro Commisso; Flavia Guzzo; Simonetta Bagella; Giulia Ceccherelli; Giovanna Becca; Maria Franca Usai; Patrizia Stipcich (Marine Biology, 2026)
Anatomical and metabolomic variability in marine plants can provide valuable insights into species adaptive strategies and resilience to environmental changes. This study explores the anatomical characteristics and metabolomic profiles of Posidonia oceanica fruits, a key Mediterranean seagrass species, collected from three areas in Sardinia (Alghero, Oristano, and Olbia). Anatomical analyses of pericarps assessed cuticle thickness and intercellular spaces. Additionally, metabolomic analyses were performed using UPLC-HRMS on both the pericarps and the seeds. Significant differences in the percentage of intercellular spaces among pericarps from the different areas were found, with those from Alghero, exhibiting a higher percentage. Metabolomic analyses highlighted distinct profiles across areas, with Alghero pericarps showing greater metabolomics complexity, characterized by high levels of chicoric acid, hydroxycinnamate and hydroxybenzoate derivatives, while seeds exhibited an abundance of procyanidins, benzoic and caffeic acids and quercetins. Interestingly, seeds from Olbia presented a higher abundance of lipids. This study provides the first comprehensive metabolomic characterization of P. oceanica pericarps and seeds, highlighting significant variability that may influence seed dispersal, germination, and species adaptability. Our findings offer new perspectives for the conservation and management of this key species, which are particularly relevant in the context of global climate change.

Effects of anthropogenic noise at population, community, habitat and ecosystem level: A global review - La Manna Gabriella; Pansini Arianna; Morello Giuseppe; Crobu Alessia; Sarà Gianluca; Ceccherelli Giulia (Next Research, 2025)

Short-term and long-term ocean acidification effects on seagrass performance: evidence from shallow CO2 vents - Arianna Pansini; Carmen Arena; Alessia Crobu; Ermenegilda Vitale; Giulia Ceccherelli (Environmental Research, 2025)

Posidonia oceanica leaf bleaching: does it affect the plant photoprotective mechanisms? - Patrizia Stipcich; Carmen Arena; Giulia Ceccherelli; Rosa Donadio; Carlos Jimenez; Vasilis Resaikos; Ermenegilda Vitale; Simonetta Fraschetti (Environmental Research, 2025)

Not only corals: seagrass bleaching in the eastern Mediterranean - Patrizia Stipcich; Carmen Arena; Giulia Ceccherelli; Rosa Donadio; Carlos Jimenez; Gabriella La Manna; Vasilis Resaikos; Ermenegilda Vitale; Simonetta Fraschetti (Science of The Total Environment, 2025)

The effects of thermal conditions and canopy density on Posidonia oceanica seedlings: implications for future seagrass restoration - Patrizia Stipcich; Arianna Pansini; Roberto Rubattu; Giulia Ceccherelli (Marine Environmental Research, 2025)

Meta-analysis reveals the effectiveness and best practices for the iconic Mediterranean seagrass restoration - Arianna Pansini; Manuel Berlino; Maria Cristina Mangano; Gianluca Sarà; Giulia Ceccherelli (Science of The Total Environment, 2025)

Different thermal regimes and susceptibility to herbivory do not constrain seagrass seedling restoration - Arianna Pansini; Patrizia Stipcich; Sara Frasca; Luciana Migliore; Giulia Ceccherelli (Marine Environmental Research, 2025)

Crustose coralline algae exhibit complex responses to breakage under current and future climate scenarios - Federico Pinna; Federica Ragazzola; Luigi Piazzi; David Evans; Jacek Raddatz; Giulia Ceccherelli (Marine Pollution Bulletin, 2024)

Spatio-temporal patterns of fish acoustic communities in Western Mediterranean coralligenous reefs: optimizing monitoring through recording duration - Gabriella La Manna; Mariangela Moro Merella; Riccardo Vargiu; Giuseppe Morello; Gianluca Sarà; Giulia Ceccherelli (Frontiers in Marine Science, 2024)
In this study, we explored the fish acoustic community at two coralligenous sites in Sardinia (Tavolara and Santa Teresa, western Mediterranean Sea) during the summer 2023. Our goal was to understand spatial and temporal patterns of fish acoustic activity on different temporal scales to offer insights for optimizing acoustic monitoring of this crucial ecosystem. We identified seventeen distinct sound types, revealing a diverse acoustic community. Tavolara had higher acoustic richness and abundance compared to Santa Teresa, which may be attributed to site-specific factors such as habitat structure, species composition, or levels of protection. Temporal analysis revealed clear diel patterns, with certain sounds associated with nocturnal or diurnal periods, reflecting the daily rhythms of different species. The study also examined how recording duration influenced acoustic richness, finding that longer recordings (15 minutes per hour and 15 minutes per hour at night) provided a more comprehensive detection of acoustic activity. Additionally, the number of recording days required to detect species richness varied depending on the site. While extended recordings improve the likelihood of detecting rare or sporadic sounds, they also present challenges in data management and equipment maintenance. The study underscores the importance of carefully planning sampling strategies to optimize acoustic monitoring and ensure effective and sustainable ecological research in coralligenous ecosystems.

The intensity of a field simulated marine heat wave differentially modulates the transcriptome expression of Posidonia oceanica from warm and cold environments - Patrizia Stipcich; Giulia Ceccherelli; Lázaro Marín-Guirao; Jessica Pazzaglia; Alex Santillán-Sarmiento; Gabriele Procaccini (Marine Biology, 2024)

How the seagrass Posidonia oceanica flowering will benefit from climate change - Patrizia Stipcich; Ivan Guala; Gabriella La Manna; Mariangela Moro Merella; Arianna Pansini; Riccardo Vargiu; Simonetta Fraschetti; Giulia Ceccherelli (Marine Pollution Bulletin, 2024)

Resistance of Posidonia oceanica seedlings to warming: Investigating the importance of the lag-phase duration between two heat events to thermo-priming - Patrizia Stipcich; Arianna Pansini; Giulia Ceccherelli (Marine Pollution Bulletin, 2024)

The resilience of transplanted seagrass traits encourages detection of restoration success - Arianna Pansini; Mario Deroma; Ivan Guala; Briac Monnier; Christine Pergent-Martini; Luigi Piazzi; Patrizia Stipcich; Giulia Ceccherelli (Journal of Environmental Management, 2024)

Warming-induced flowering and fruiting in the seagrass Posidonia oceanica and uncertainties due to context-dependent features - Patrizia Stipcich; Gabriella La Manna; Giulia Ceccherelli (Marine Biology, 2024)
This study explores the impacts of global warming on the reproductive efforts of Posidonia oceanica , a key seagrass species endemic to the Mediterranean Sea. By analyzing data from five areas in Sardinia in February 2023, we have investigated the relationship between thermal descriptors and P. oceanica flowering and fruiting variables. In fact, whether climate change has been affected the distribution of seagrasses by changing their reproductive efforts is still controversial and our findings contribute to this ongoing debate, highlighting a noticeable increase in reproductive events potentially affected by rising temperature. Overall, mean summer sea surface temperature (SST) was positively associated to inflorescence density, presence of living fruits and fruit size; living fruits and fruit size were also influenced positively by the maximum SST within 3 months before sampling (November–February). Both flowering and fruiting were negatively affected by the maximum SST within 1 month before inflorescence observation and mean winter SST, respectively, suggesting that P. oceanica reproductive effort depends on the duration and the temporal context in which the anomaly occurs. However, the high variability between meadows of the same area highlights the need of future studies to focus on the uncertainties related to local factors.

Cultivable mycoflora on bleached, decaying and healthy Posidonia oceanica leaves in a warm-edge Mediterranean location - Patrizia Stipcich; Virgilio Balmas; Carlos E. Jimenez; Safa Oufensou; Giulia Ceccherelli (Marine Environmental Research, 2023)

Not only wide range shifts: Marine warming and heat waves influence spatial traits of a mediterranean common bottlenose dolphin population - Gabriella La Manna; Fabio Ronchetti; Francesco Perretti; Giulia Ceccherelli (Estuarine, Coastal and Shelf Science, 2023)

Experimental thermocline deepening highlights the resilience of the seagrass Posidonia oceanica: An opportunity to investigate shoot adaptability - Patrizia Stipcich; Vasilis Resaikos; Giulia Ceccherelli (Marine Pollution Bulletin, 2023)

Field development of Posidonia oceanica seedlings changes under predicted acidification conditions - Arianna Pansini; Pedro Beca-Carretero; Manuel Berlino; Gianluca Sarà; Dagmar B. Stengel; Patrizia Stipcich; Giulia Ceccherelli (Marine Environmental Research, 2023)

Effects of high temperature and marine heat waves on seagrasses: Is warming affecting the nutritional value of Posidonia oceanica? - Patrizia Stipcich; Pedro Beca-Carretero; Xosé Antón Álvarez-Salgado; Eugenia T. Apostolaki; Niki Chartosia; Pavlos Theofilos Efthymiadis; Carlos E. Jimenez; Gabriella La Manna; Arianna Pansini; Elena Principato; Vasilis Resaikos; Dagmar B. Stengel; et al. (Marine Environmental Research, 2023)

The Mediterranean bioconstructor Lithophyllum stictiforme shows adaptability to future warming - Federico Pinna; Annalisa Caragnano; Luigi Piazzi; Federica Ragazzola; Patrizia Stipcich; Fabio Rindi; Giulia Ceccherelli (Frontiers in Marine Science, 2022)
Understanding how coralline algae may acclimatize to ocean warming is important to understand their survival over the coming century. Taking advantage of natural differences in temperature conditions between coastal areas in Sardinia (Italy) and between depths, the responses in terms of biological traits to warming of the crustose coralline alga Lithophyllum stictiforme , a key bioconstructor of coralligenous reefs in the Mediterranean, were evaluated in the field by two innovative transplant experiments where translocated specimens were used as controls. Results of the first experiment (algae cross transplanted between a cold and a warm site at two depths, 23 and 34 m) showed that the marginal growth of the alga and production of conceptacles were higher in the cold site, regardless of the treatment (transplant and translocation) and depth. However, growth in thickness in algae transferred from the cold to the warm site was higher at 34 m of depth, where they had a better performance than the local (translocated) algae. Results of the second experiment (algae transplanted from 34 m to 15 m of depth under different light irradiance manipulations) evidenced that the increase in temperature of +4°C was tolerated by thalli transplanted at 15 m, but that thallus growth and conceptacles production was negatively affected by the higher light irradiance. These results suggest an overall good adaptability of L. stictiforme under warmer conditions, even those due to thermocline deepening. Overall, these results encourage consideration of the use of transplants of this bioconstructor in future restoration actions of coralligenous habitats.

Assessment of Posidonia oceanica traits along a temperature gradient in the Mediterranean Sea shows impacts of marine warming and heat waves - Patrizia Stipcich; Eugenia T. Apostolaki; Niki Chartosia; Pavlos Theofilos Efthymiadis; Carlos E. Jimenez; Gabriella La Manna; Arianna Pansini; Elena Principato; Vasilis Resaikos; Giulia Ceccherelli (Frontiers in Marine Science, 2022)
Global warming and Marine Heat Waves (MHWs) are having large-scale impacts on the seagrasses and their effects on the Mediterranean endemic Posidonia oceanica need to be properly defined. This research aimed to sharpen the knowledge on P. oceanica response to the warming by correlating the shoot morphology and the productivity of the seagrass to temperature conditions and MHW occurrence. Two correlative studies, along a Mediterranean temperature range (sites at the same latitude), were conducted: one explored the associations of summer 2021 Sea Surface Temperature (SST) and MHWs on P. oceanica morphology and the other used a reconstruction technique (lepidochronological analysis) to relate past temperature conditions and MHW occurrence to proxies of seagrass productivity for the corresponding periods. The results showed that the mean summer temperature affected the P. oceanica leaf necrosis and that MHWs occurrence changed the morphology of the plant by lowering the leaf area and increasing leaf necrosis. Interesting results were also found relating the past thermal environment, since rhizome biomass has been negatively affected by the number of MHWs and rhizome length by the temperature range. This research provides fundamental insights about P. oceanica changes linked to warming and MHWs, identifying the potential plant indicators assisting future experimental and modelling studies. To the best of our knowledge, this is the first time a reconstruction technique is used to evaluate the effects of past MHWs on the morphology and productivity of a plant species.

Marine heatwaves drive recurrent mass mortalities in the Mediterranean Sea - Joaquim Garrabou; Daniel Gómez‐Gras; Alba Medrano; Carlo Cerrano; Massimo Ponti; Robert Schlegel; Nathaniel Bensoussan; Eva Turicchia; Maria Sini; Vasilis Gerovasileiou; Nuria Teixido; Alice Mirasole; et al. (Global Change Biology, 2022)
Climate change is causing an increase in the frequency and intensity of marine heatwaves (MHWs) and mass mortality events (MMEs) of marine organisms are one of their main ecological impacts. Here, we show that during the 2015–2019 period, the Mediterranean Sea has experienced exceptional thermal conditions resulting in the onset of five consecutive years of widespread MMEs across the basin. These MMEs affected thousands of kilometers of coastline from the surface to 45 m, across a range of marine habitats and taxa (50 taxa across 8 phyla). Significant relationships were found between the incidence of MMEs and the heat exposure associated with MHWs observed both at the surface and across depths. Our findings reveal that the Mediterranean Sea is experiencing an acceleration of the ecological impacts of MHWs which poses an unprecedented threat to its ecosystems' health and functioning. Overall, we show that increasing the resolution of empirical observation is critical to enhancing our ability to more effectively understand and manage the consequences of climate change.

Performance of a baited underwater video system vs. the underwater visual census technique in assessing the structure of fish assemblages in a Mediterranean marine protected area - GABRIELLA LA MANNA; IVAN GUALA; DANIELE GRECH; FRANCESCO PERRETTI; FABIO RONCHETTI; MICHELE MANGHI; ALBERTO RUIU; GIULIA CECCHERELLI (Mediterranean Marine Science, 2021)
Accurate, rapid and cost-effective fish assemblage monitoring is fundamental for marine protected area (MPA) management as a pivotal tool to verify whether and to what extent MPA conservation objectives have been achieved and to redefine these objectives in the framework of an adaptive management. Recently, there has been a sharp increase in the number of video-based methods to study fish fauna, such as baited remote underwater video (BRUV) systems, that, depending on the objectives of the monitoring, can provide complementary or additional data to the more commonly used underwater visual census (UVC). Even though BRUV systems have been widely used in a wide range of geographic contexts and habitats, their use in the Mediterranean basin is still sporadic and the evaluation of the efficiency of BRUV systems and whether they can be used to complement other techniques needs investigation. Thus, the objective of this study was to assess the performance of a BRUV system in a Mediterranean MPA and to evaluate its effectiveness in assessing the structure of fish assemblages (abundance and species richness) by comparing estimates with those obtained by the UVC technique. The fish fauna were monitored by BRUV and UVC in the Capo Caccia – Isola Piana Marine Protected Area (Sardinia, Italy), in July and October-November 2020, at four sampling sites and two areas, hundreds of meters apart, for each site. Overall, 46 taxa and a total of 3620 individuals were observed by BRUV, while 36 taxa and a total of 2995 individuals were observed by UVC. The species first observed in front of the camera’s field of view and able to reach the maximum abundance were the planktivores (Chromis chromis and Oblada melanura) followed by several carnivorous species belonging to the families Labridae, Serranidae and Sparidae, and lastly two carnivores (Mullus surmuletus and Mugilidae spp.) and some high-level predators (Dentex dentex, Seriola dumerili, Sphyraena viridensis, Dicentrarchus labrax). The maximum species richness and abundance were reached between 39 and 50 min. The cumulative species richness increased until around 30 min. Species richness was higher during the BRUV compared to the UVC monitoring. The consistency in findings between BRUV and UVC and a better performance of BRUV in detecting some species (mainly high-level predators), supports BRUV as an additional technique for describing and quantifying species richness and abundance also in the Mediterranean Sea. Based on the results of this study, the advantages/disadvantages, shortcomings, suggestions and resources needed for the two techniques are outlined.

Common Bottlenose Dolphin Protection and Sustainable Boating: Species Distribution Modeling for Effective Coastal Planning - Gabriella La Manna; Fabio Ronchetti; Gianluca Sarà; Alberto Ruiu; Giulia Ceccherelli (Frontiers in Marine Science, 2020)

Modeling Macroalgal Forest Distribution at Mediterranean Scale: Present Status, Drivers of Changes and Insights for Conservation and Management - Erika Fabbrizzi; Michele Scardi; Enric Ballesteros; Lisandro Benedetti-Cecchi; Emma Cebrian; Giulia Ceccherelli; Francesco De Leo; Alan Deidun; Giuseppe Guarnieri; Annalisa Falace; Silvia Fraissinet; Chiara Giommi; et al. (Frontiers in Marine Science, 2020)

Impact assessment of fish cages on coralligenous reefs through the use of the STAR sampling procedure - LUIGI PIAZZI; ENRICO CECCHI; MARIA FRANCESCA CINTI; PATRIZIA STIPCICH; GIULIA CECCHERELLI (Mediterranean Marine Science, 2019)
The study aimed at contributing to the development of methods to assessing the effects of human disturbance on coralligenous reefs. The effects of the presence of a fish farm on coralligenous reefs were evaluated using the STAR (STAndaRdized coralligenous evaluation procedure) sampling procedure. An asymmetrical sampling design was used to compare the aquaculture site with two reference sites in areas unaffected by human pressure. The response of different ecological indices (ESCA, Ecological Status of Coralligenous Assemblages; ISLA, Integrated Sensitivity Level of coralligenous Assemblages; COARSE, COralligenous Assessment by Reef Scape Estimate) and descriptors (α-diversity, β-diversity and Sensitivity Level) of this kind of disturbance was compared. Results indicate that coralligenous reefs are vulnerable to aquaculture fish cages, and differences in the structure of coralligenous assemblages between the disturbed and the reference sites were mostly due to the decrease in β-diversity. On the contrary, no significant differences in the number of taxa/groups were highlighted. Encrusting Corallinales, erect Rhodophyta, Dictyotales, Fucales and Halimeda tuna were more abundant in reference sites than in disturbed site, while Peyssonnelia spp. and algal turfs had the opposite trend. Conversely, no significant differences between conditions were found in the abundance of sessile invertebrates. The study supports the suitability of the STAR approach to be employed in impact evaluation assessments, such as in monitoring programs. The present study is a first attempt to combine three different ecological indices (ESCA, ISLA and COARSE) within a unified approach, in order to assess the status of coralligenous reefs subjected to a moderate human-induced disturbance. The inconsistent response of the different indices highlights the advantage of applying different indices and descriptors to evaluate the variable human pressures on natural systems.

Influence of environmental, social and behavioural variables on the whistling of the common bottlenose dolphin (Tursiops truncatus) - Gabriella La Manna; Nikolina Rako-Gòspic; Michele Manghi; Giulia Ceccherelli (Behavioral Ecology and Sociobiology, 2019)

Seagrass collapse due to synergistic stressors is not anticipated by phenological changes - Giulia Ceccherelli; Silvia Oliva; Stefania Pinna; Luigi Piazzi; Gabriele Procaccini; Lazaro Marin-Guirao; Emanuela Dattolo; Roberto Gallia; Gabriella La Manna; Paola Gennaro; Monya M. Costa; Isabel Barrote; et al. (Oecologia, 2018)

A few is enough: a low cover of a non-native seaweed reduces the resilience of Mediterranean macroalgal stands to disturbances of varying extent - Fabio Bulleri; Lisandro Benedetti-Cecchi; Giulia Ceccherelli; Laura Tamburello (Biological Invasions, 2017)

The role of floating mucilage in the invasive spread of the benthic microalga Chrysophaeum taylorii - Sarah Caronni; Maria Anna Delaria; Kirsten Heimann; Giovanni Macri; Augusto Navone; Pieraugusto Panzalis; Giulia Ceccherelli (Marine Ecology, 2016)
Chrysophaeum taylorii Lewis & Bryan (Pelagophyceae) is a mucilage‐producing benthic microalga that has recently begun to spread in the Mediterranean Sea, where a range expansion is occurring. This paper presents the results of three field experiments that aimed to increase the knowledge on mucilage provision mechanisms for this benthic microalga and to evaluate the importance of mucilage in its range expansion. By means of two correlative field experiments (several years of data were considered to encompass the variability of mucilage cover) we found that, on the sea bottom, mucilage cover does not depend on epilithic cell density and that both its cover and settling are affected by water flow. We also tested the hypothesis that cells embedded in floating mucilage fall on the underlying substratum, where their abundance depends on water flow. To this aim, in the field we manipulated the presence of floating mucilaginous aggregates in cages with different levels of exposure to winds. The abundance of C. taylorii cells on the substratum under cages with mucilage was compared with that of two control treatments: cages without mucilage and mucilage in still water, in the field and lab, respectively. The results suggested that mucilage can represent an excellent strategy for the species to disperse, as C. taylorii cells fall from the floating mucilage and, if the water flow is unimportant, settle on hard substrata just underneath the cage. This study enriches the portfolio of knowledge of the dispersal strategies of microalgae and contributes to the understanding of the spread of invasive species.

Epiphyte assemblages of the Mediterranean seagrass Posidonia oceanica : an overview - Luigi Piazzi; David Balata; Giulia Ceccherelli (Marine Ecology, 2016)
This paper reviews the main studies dealing with epiphytes of both leaves and rhizomes of Posidonia oceanica , the main seagrass found in the Mediterranean Sea. A total of 660 epiphyte species has been recorded, including 430 on leaves and 437 on rhizomes. Of these, 205 are Rhodophyta, 59 Ochrophyta, 43 Chlorophyta, 78 Porifera, 82 Cnidaria, 19 Annelida, 155 Bryozoa and 19 Tunicata. The epiphyte assemblages demonstrate a gradient of dissimilarity from west to east, with the eastern area being the most unlike the others. The differences can be attributed mostly to rare species that differ amongst the Mediterranean regions. Many of the dominant taxa have been found in all meadows studied. Data concerning species composition, abundance, and patterns of spatial and temporal variability are summarized, and biotic and abiotic factors controlling the structure of assemblages are discussed. Responses of epiphyte assemblages to anthropogenic stressors, such as nutrient enrichment and biological invasions, are discussed in relation to the use of epiphytes as ecological indicators.

The role of disturbance in promoting the spread of the invasive seaweed Caulerpa racemosa in seagrass meadows - Giulia Ceccherelli; Stefania Pinna; Valentina Cusseddu; Fabio Bulleri (Biological Invasions, 2014)

Relevant scales of variability of the benthic allochthonous microalga Chrysophaeum taylorii - Sarah Caronni; Maria Anna Delaria; Augusto Navone; Pieraugusto Panzalis; Nicola Sechi; Giulia Ceccherelli (Marine Biology, 2014)

Caulerpa racemosa var. cylindracea as a potential source of organic matter for benthic consumers: evidences from a stable isotope analysis - Daniela Casu; Giulia Ceccherelli; Nicola Sechi; Paola Rumolo; Gianluca Sarà (Aquatic Ecology, 2009)

Immediate Effects of Experimental Human Trampling on Mid-Upper Intertidal benthic Invertebrates at the Asinara Island MPA (NW Mediterranean) - Daniela Casu; Giulia Ceccherelli; Alberto Castelli (Hydrobiologia, 2006)

Nutrient availability in the sediment and the reciprocal effects between the native seagrass Cymodocea nodosa and the introduced rhizophytic alga Caulerpa taxifolia - Giulia Ceccherelli; Nicola Sechi (Hydrobiologia, 2002)